Strategi LKC Dompet Dhuafa Jawa Tengah Dalam Mendukung Pencapaian SDG’s Melalui Program Kawasan Sehat (Studi Kasus Penerapan Biodigester di Desa Suro, Kab. Banyumas) - Adila Nur Maylani; Chandra Warsito; Titi Ngudiati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Sustainable development is a global issue that requires the active involvement of various parties, including social institutions, in supporting the achievement of the Sustainable Development Goals (SDGs). This study aims to analyze the strategy of the Lembaga Kesehatan Cuma-Cuma (LKC) Dompet Dhuafa Central Java in promoting healthy areas through the implementation of biodigester technology in Suro Village, Kalibagor District, Banyumas Regency. This research uses a qualitative method with a field study approach to obtain descriptive data from LKC representatives, community leaders, and local residents. Data were collected through observation, in-depth interviews, and documentation involving six informants. The findings show that LKC's strategy includes community education and empowerment in managing livestock waste, the construction of biodigester installations as a solution for waste processing and an alternative energy source, and collaboration with the village government and local partners to ensure program sustainability. This strategy contributes to the achievement of several SDGs goals, particularly in the areas of health, sanitation, clean energy, climate action, and partnerships. The implication of this study indicates that an environmentally friendly technology-based approach can encourage social transformation, improve environmental quality, and strengthen stakeholder collaboration at the village level.